Level of Self-Regulated Learning of Students at Takhassus Elementary School Al-Qur’an Kalibeber Wonosobo - Fajar Dwi Mukti; Ayu Sholina (Faculty of Education and Teacher Training of UINSI Samarinda, 2022)
This study is motivated by the low interpersonal and intrapersonal skills of students indicated by students who tend to be quiet, difficult to get along with peers, bullying, and some students have a low ability to understand lessons, affecting their learning achievement. This study aimed to determine the level of self-regulated learning of students in class VI B of SD Takhassus Al-Quran Kalibeber Wonosobo. The research method used in this study was mixed. For the quantitative approach, the researcher used a population sampling technique by taking all samples in the population. In contrast, the qualitative approach was used to deepen the data through interviews using purposive sampling techniques. The results showed that the level of self-regulated learning of students was in the high category with a frequency of 7 respondents (23.33 %), in the medium category with a frequency of 21 respondents (70%), in the low category with a frequency of 2 respondents (6.66%). Thus, it can be concluded that the level of self-regulated learning of students is moderate (70%). This is proven by the results of data collection showing several indicators such as students having self-awareness of the need for self-regulated learning and knowledge for their own needs as learners. They can also focus their attention on ongoing learning, evaluate and monitor themselves in learning, make learning plans, and have enthusiasm for achieving learning goals. These results indicate that self-regulated learning is correlated with student achievement.